THE DISSOLUTION OF CALCITE IN AQUEOUS ACID - THE INFLUENCE OF HUMIC SPECIES - Compton, R; Sanders, G (1993)
The kinetics of proton-induced calcite dissolution in aqueous solution in the presence of humic acids and their sodium salts are reported. In equilibrated acid solutions (pH < 4) there is no inhibition by humic material and dissolution proceeds at a rate simply determined by the solution pH. Contrastingly the sodium salts of humic acids were found to have a significant inhibitory effect on the acid catalyzed dissolution. This was quantified using a novel channel flow cell experiment which employed two electrodes, the upstream of which was used to inject protons into a neutral solution, which also contained sodium salts of humic acid, via electrolytic oxidation of dissolved hydroquinone. The two electrodes were located immediately upstream and downstream of a calcite crystal so that the proton injection served to dissolve the calcite in the (inhibiting) presence of humic salts unequilibrated with the solution pH. The amount of H+ which survived passage to the downstream "detector" electrode was used to quantify the rate of dissolution and hence the inhibitory effects of the humic acid. The latter were found to operate in a manner not inconsistent with Langmuirian adsorption. © 1993 Academic Press. All rights reserved.